EKSPLORASI RUMAH ADAT OMO HADA NIAS UTARA TERHADAP KONSEP GEOMETRI - agustina agustina c b sihite (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2022)
Culture is a tradition that has been passed down from generation to generation. Culture is what shows the customs or traditions in an area. Culture is closely related to society. Ethnomathematics is one alternative that links culture and mathematics. Ethnomathematics also plays an important role in exploring noble values ​​in the culture of the community. This study has the aim of the researcher being to describe and document the results of the ethnomathematical exploration of the geometric concept of the Omo Hada traditional house building. The type of research used in this research is qualitative research. Data collection techniques used are observation, interviews and documentation. There are several geometric concepts in the design of the Omo Hada traditional house, namely the concept of flat wake, the concept of building a flat side space, the concept of the relationship between lines, the concept of angles, and geometric transformations. The results of the study are expected to help teachers explain mathematical concepts as well as introduce the culture of the Omo Hada Traditional House